Synthesis of Certain New Morpholine Derivatives Bearing a Thiazole Moiety - Nurcan Berber (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Morpholineis a synthetic simple heterocyclic organic compound having characteristicfunctional groups of amine and ether. Feasible physicochemical properties(polarity and solubility), low cost and wide availability make it a suitablecandidate for the synthesis of many potent drugs. In our work, we weresynthesized a new series of thiazole substituted morpholine derivatives in twosteps. In the first stage, thiourea was synthesized and the formation ofthiazole ring at the other stage was ensured.